Research and Analysis on the Application of BIM Technology in Municipal Tunnel Engineering Design - Lie, Gangfeng (Journal of Theory and Practice of Engineering Science, 2023)
As a special kind of municipal engineering, municipal tunnel engineering not only has the characteristics of complex structure and high safety risks, but also needs to comprehensively apply various special construction technologies in the design stage, and fully consider the terrain, tectonics, vehicle access, tunnel support and other factors, which is relatively difficult to design. Therefore, BIM technology is applied to the design of municipal tunnel engineering, It can help relevant designers successfully solve various design problems and provide guarantees for the rationality of engineering design schemes. Based on this, from the perspective of rational design of municipal tunnel engineering, the advantages and effects of BIM technology are analyzed, and specific discussions are conducted around the application points of BIM technology in municipal tunnel engineering design work, in order to provide some inspiration for relevant designers.